2018
DOI: 10.1007/s11258-018-0865-8
|View full text |Cite
|
Sign up to set email alerts
|

Reaching new heights: can drones replace current methods to study plant population dynamics?

Abstract: Spatially explicit data on heterogeneously distributed plant populations are difficult to quantify using either traditional field-based methods or remote sensing techniques alone. Unmanned Aerial Vehicles (UAVs) offer new means and tools for baseline monitoring of such populations. We tested the use of vegetation classification of UAV-acquired photographs as a method to capture heterogeneously distributed plant populations, using Jacobaea vulgaris as a model species. Five sites, each containing 1-4 pastures wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 44 publications
(45 reference statements)
2
29
0
Order By: Relevance
“…However, the accuracy of juniper sapling identification varied between seasons. Similar to the results found by Tay et al [39], we found that pixel-based classification applied to UAV images can accurately detect and monitor vegetation. Given the large scale of juniper expansion and time requirements associated with ground surveys, the use of UAV offers the advantage of more efficient data collection compared to using ground-based techniques alone.…”
Section: Study Limitations and Future Researchsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the accuracy of juniper sapling identification varied between seasons. Similar to the results found by Tay et al [39], we found that pixel-based classification applied to UAV images can accurately detect and monitor vegetation. Given the large scale of juniper expansion and time requirements associated with ground surveys, the use of UAV offers the advantage of more efficient data collection compared to using ground-based techniques alone.…”
Section: Study Limitations and Future Researchsupporting
confidence: 90%
“…Another example of an index potentially useful in studying western juniper is the total ratio vegetation index (TRVI) [34], which was developed to address different vegetation characteristics in arid and semiarid ecosystems (e.g., juniper woodlands).Other techniques used in image analysis such as classification have been utilized extensively for the detection and assessment of vegetation [35][36][37]. Pixel-based image analysis has been used for weed detection [38] and vegetation identification in mixed plant communities [39]. The use of classification tools for image analysis has also been shown to decrease time requirements compared to manual analysis of imagery [40], particularly over large areas.…”
mentioning
confidence: 99%
“…There are apparently few studies carried out with the goal of identifying or quantifying native herbaceous species from drone imagery [12,[23][24][25][26][27]. These studies were implemented at a range of spatial and spectral resolutions with varying degrees of sophistication and mixed results.…”
Section: Introductionmentioning
confidence: 99%
“…Typically, higher spatial resolution comes at the expense of lower geographical coverage as it generally depends on flight height. However, such ultra-high-resolution data captured on demand allow researchers to investigate microclimatic differentiation at the scale of single plant individuals within an entire landscape ( Figure 2; Cruzan et al, 2016;Cunliffe, Brazier, & Anderson, 2016;Tang & Shao, 2015;Tay, Erfmeier, & Kalwij, 2018;Wich & Koh, 2018 (Meyer, Weigelt, et al, 2016).…”
Section: Ag G Reg Ati On Of L Arg E Data S E Tsmentioning
confidence: 99%